Successful late treatment of venous air embolism with hyperbaric oxygen. Issue 776 (June 1990) - Dunbar, E. M.; Fox, R.; Watson, B.; Akrill, P.
Abstract : A case of haemodialysis-associated venous air embolism is described. The patient commenced hyperbaric oxygen therapy 21 hours after the event when, despite appearing decerebrate, he made a complete recovery. This case underlines the importance of all clinicians being aware of those centres with facilities for hyperbaric therapy and the need to refer all patients with cerebral air embolism even following a prolonged delay.